Face‐centred finite volume methods for Stokes flows with variable viscosity - Rubén Sevilla (International Journal for Numerical Methods in Engineering, 2024)
Six face-centred finite volume formulations are derived and compared for the simulation of Stokes flows with spatially varying viscosity. The main difference between the methods derived is the mixed variable used in the mixed formulation and the use of a weak or strong form in each element using integration by parts. A brief discussion about the properties of the different methods is provided, including comments on the computational cost and the symmetry of the resulting global system of equations. Finally, numerical examples in two and three dimensions are used to compare the accuracy of all the formulations presented. The examples include a problem where the methods are employed to simulate a steep variation of the viscosity, showing the ability to perform these simulations without using a mesh conforming to a material interface. The performance of different element types and different choices of the stabilisation is also discussed.